2021
DOI: 10.3389/fimmu.2020.616044
|View full text |Cite
|
Sign up to set email alerts
|

Trem-2 Promotes Emergence of Restorative Macrophages and Endothelial Cells During Recovery From Hepatic Tissue Damage

Abstract: Macrophages are pivotal in mounting liver inflammatory and tissue repair responses upon hepatic injury, showing remarkable functional plasticity. The molecular mechanisms determining macrophage transition from inflammatory to restorative phenotypes in the damaged liver remain unclear. Using mouse models of acute (APAP) and chronic (CCl4) drug-induced hepatotoxic injury we show that the immune receptor Trem-2 controls phenotypic shifts of liver macrophages and impacts endothelial cell differentiation during tis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 49 publications
4
34
1
Order By: Relevance
“…Mice treatment with ICOS-Fc also allows the full clearance of centrilobular necrosis. The involvement of MoMFs expressing MerKT and TREM-2 receptors in the recovery from acute liver injury is consistent with the notion that both MerKT or TREM-2 are required for damping macrophage proinflammatory functions and promoting the clearance of apoptotic cells (24,25,30). Moreover, recent reports have shown that mice deficient in either MerKT or TREM-2 suffer a delayed resolution of acetaminophen hepatotoxicity (24,25,30).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Mice treatment with ICOS-Fc also allows the full clearance of centrilobular necrosis. The involvement of MoMFs expressing MerKT and TREM-2 receptors in the recovery from acute liver injury is consistent with the notion that both MerKT or TREM-2 are required for damping macrophage proinflammatory functions and promoting the clearance of apoptotic cells (24,25,30). Moreover, recent reports have shown that mice deficient in either MerKT or TREM-2 suffer a delayed resolution of acetaminophen hepatotoxicity (24,25,30).…”
Section: Discussionsupporting
confidence: 86%
“…The analysis of the transcripts for markers of reparative MoMFs such as the mannose receptor (CD206) and the efferocytosis receptor c-Met Proto-Oncogene Tyrosine Kinase (MerTK) (9), evidenced that the expression of both markers was dramatically reduced during acute inflammation and recovered to control values during liver repair (Figure 4). Similarly, hepatic healing was associated with the up-regulation in the Triggering Receptor Expressed on Myeloid cells 2 (TREM-2) (Figure 4), a plasma membrane receptor involved in the damping MoMF inflammatory response (24,25). In these settings, ICOS -/mice were less efficient than WT animals in up-regulating CD206, MerTK and TREM-2 (Figure 4).…”
Section: Icos Signaling Is Required For the Reparative Response Of Liver Macrophagesmentioning
confidence: 98%
“…Various paracrine and autocrine interactions were detected between their ligands and endothelial cell cognate receptors. In line with Perugorria et al [89], we have recently shown that in acute and chronic mouse models of liver disease, Trem-2 is particularly upregulated in a specific macrophage population, named "transition macrophages" [99]. Transcriptomic analyses showed that absence of Trem-2 impacts the switching from recruited to transition macrophages, with the latter showing muted transcriptional response to oxidative stress and an inability to shut down the inflammatory profile.…”
Section: Trem-2 As a Likely Mediator Of Macrophage/monocyte-endothelial Cell Interactionssupporting
confidence: 81%
“…Interestingly, an endothelial liver damage endothelial cell (LDECs) population showing a distinct transcriptional profile was identified. The accumulation of LDECs significantly correlated to the degree of liver damage and to impaired replenishment of KC compartment [99] (Figure 2). These results fit the notion that a crosstalk between macrophages and endothelial cells is part of the liver regeneration process after liver injury.…”
Section: Trem-2 As a Likely Mediator Of Macrophage/monocyte-endothelial Cell Interactionsmentioning
confidence: 95%
“…Trem2 + macrophages have previously been shown to be involved in lipid metabolism and the regulation of hair follicle stem cell activity, pointing to an important role in skin regeneration ( 55 ). Moreover, the regenerative action of Trem2 + macrophages has been previously corroborated in other organ systems, such as during colonic mucosal healing or liver regeneration where Trem2 + macrophages promote regenerative endothelial cell differentiation ( 56 , 57 ). Variants in the Trem2 locus are associated with early-onset Alzheimer’s disease in humans, related to a reduced clearance of extracellular amyloid β–containing plaques due to an impaired function of microglia within the brain ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 76%